Tiny genomes and endoreduplication in Strepsiptera - Johnston, J; Ross, L; Beani, L; Hughes, D; Kathirithamby, J (Wiley, 2004)
Using flow cytometry, the genome sizes of two species of Strepsiptera were studied: that of male Caenocholax fenyesi texensis Kathirithamby & Johnston (Myrmecolacidae) at 108 Mb, which is the smallest insect genome documented to date; and those of male and female Xenos vesparum Rossi (Stylopidae), which are 1C = 130 and 133 Mb, respectively. The genome sizes of the following were analysed for comparative purposes: (a) the Hessian fly, Mayetiola destructor (Say), which was previously reported to be the smallest among insects: the male measured at 1C = 121 Mb and the female at 1C = 158 Mb; and (b) the female parasitic, haplodiploid, microhymenopteran wasp, Trichogramma brassicae Bezdenko, which measured at 1C = 246 Mb. The hosts of the strepsipterans were also measured: male Solenopsis invicta Buren, the red imported fire ant (host of male C. f. texensis), which is 1C = 753.3 Mb, and female Polistes dominulus Christ, the paper wasp (host of X. vesparum), is 1C = 301.4 Mb. Endoreduplication (4C) of the genome of the thorax of the male strepsipteran, and higher levels of endoduplication (4, 8, 16C) in the body of the larger female was observed. In contrast, little or no endoreduplication was observed, either in the Hessian fly, or in the parasitic wasp.